The efficacy and safety of conventional transcatheter arterial chemoembolization combined with PD-1 inhibitor and anti-angiogenesis tyrosine kinase inhibitor treatment for patients with unresectable hepatocellular carcinoma: a real-world comparative study - Guo, Zheng; Zhu, Huabin; Zhang, Xiufang; Huang, Li; Wang, Xiangcai; Shi, Huaqiu; Yu, Li; Qiu, Yingwei; Tu, Fuping (Frontiers in Oncology, 2022)
Aim We sought to evaluate the efficacy and safety of conventional transcatheter arterial chemoembolization (cTACE) sequentially combined with systemic treatment by programmed cell death protein 1 (PD-1) inhibitor and anti-angiogenesis tyrosine kinase inhibitor (Anti-angiogenesis TKI) in patients with unresectable hepatocellular carcinoma (HCC). Materials and methods One hundred and forty-seven advanced HCC patients who received PD-1 inhibitors and TKIs as first-line systemic treatment between August 2019 and April 2021 were collected retrospectively. Fifty-four patients were finally included and divided into cTACE and no-cTACE groups, according to whether cTACE treatment was performed within 8 weeks before systemic treatment. The tumor objective response ratio (ORR), progression-free survival (PFS), overall survival (OS), and adverse events (AEs) were compared between the groups. Significant factors affecting PFS and OS were determined by Cox regression. Results Thirty-one patients received cTACE followed by systemic treatment and 23 patients received systemic treatment only. The ORRs of the cTACE group were 48.4% (after two cycles of systemic treatment) and 51.6% (after four cycles of systemic treatment), while those of the no-cTACE group were only 17.4% and 21.7%. cTACE patients also had a longer median PFS (11.70 vs. 4.00 months, P = 0.031) and median OS (19.80 vs. 11.6 months, P = 0.006) than no-cTACE patients. Regression analyses indicated that cTACE therapy and Eastern Cooperative Oncology Group performance status were independent risk factors for PFS and OS. AEs by type were similar between the cTACE and no-cTACE groups, except for liver function injury, which was more common among cTACE patients. Fourteen patients suffered with grade 1-2 of rash in 21 patients with objective response, while only 10 patients suffered with rash in 33 patients without objective response, the adjusted hazard ratio (HR) was 4.382 (1.297–14.803). Conclusions The combination of cTACE and PD-1 inhibitors and anti-angiogenesis TKIs as therapy significantly improved markers of treatment efficacy, including ORR, PFS, and OS, in unresectable HCC patients, while no more serious AEs recorded in this population compared to those receiving systemic treatment alone. Skin rash might be a predict factor to the efficacy of PD-1 inhibitors and TKI treatment.